MOTIVATION AND LANGUAGE LEARNING STRATEGIES (INTERNATIONAL JOURNAL OF SCIENCE AND TECHNOLOGY, 2025)
This theme explores how motivation influences the selection and use of language learning strategies. It examines the interplay between intrinsic and extrinsic motivation and their impact on learners’ ability to adopt cognitive, metacognitive, affective, and social strategies. The theme also highlights how strategic learning can, in turn, enhance motivation, creating a cycle of continuous language improvement. Understanding this relationship can help educators and learners optimize language acquisition by fostering motivation and implementing effective learning techniques.